2013
DOI: 10.1089/vbz.2012.1054
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Borne Pathogens in Ticks Feeding on Migratory Passerines in Western Part of Estonia

Abstract: During southward migration in the years [2006][2007][2008][2009] 178 migratory passerines of 24 bird species infested with ticks were captured at bird stations in Western Estonia. In total, 249 nymphal ticks were removed and analyzed individually for the presence of Borrelia burgdorferi sensu lato (s.l.), tick-borne encephalitis virus (TBEV), and Anaplasma phagocytophilum. The majority of ticks were collected from Acrocephalus (58%), Turdus (13%), Sylvia (8%), and Parus (6%) bird species. Tick-borne pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 35 publications
6
39
0
11
Order By: Relevance
“…Birds were shown to be important mobile hosts responsible for the spread of one or more stages of ticks and tick-borne pathogens such as Rickettsia, Borrelia, Anaplasma and Ehrlichia (ANDERSON et al, 1896;PARKER et al, 1933;HOOGSTRAAL, 1961;1963;SOMOV;SOLDATOV, 1964apud HUBÁLEK 2004OLSEN et al, 1993;GERN et al, 1998;HUMAIR et al, 1998;ALEKSEEV et al, 2001;BJÖERSDORFF et al, 2001;DANIELS et al, 2002;SANTOS-SILVA et al, 2006;SMITH et al, 2006;OGDEN et al, 2008;HAMER et al, 2011;GELLER et al, 2013;NORTE et al, 2013;LITERAK et al, 2015).…”
Section: Outside Of Brazil Mainly In Europe and Northmentioning
confidence: 99%
See 1 more Smart Citation
“…Birds were shown to be important mobile hosts responsible for the spread of one or more stages of ticks and tick-borne pathogens such as Rickettsia, Borrelia, Anaplasma and Ehrlichia (ANDERSON et al, 1896;PARKER et al, 1933;HOOGSTRAAL, 1961;1963;SOMOV;SOLDATOV, 1964apud HUBÁLEK 2004OLSEN et al, 1993;GERN et al, 1998;HUMAIR et al, 1998;ALEKSEEV et al, 2001;BJÖERSDORFF et al, 2001;DANIELS et al, 2002;SANTOS-SILVA et al, 2006;SMITH et al, 2006;OGDEN et al, 2008;HAMER et al, 2011;GELLER et al, 2013;NORTE et al, 2013;LITERAK et al, 2015).…”
Section: Outside Of Brazil Mainly In Europe and Northmentioning
confidence: 99%
“…Migratory birds in particular have received much attention as they can transport potentially infected ticks across large areas and may account for the origin of some new foci of diseases (ANDERSON et al, 1986;OLSEN et al, 1995a;KLICH et al, 1996;SMITH et al, 1996;RAND et al, 1998;KINSEY et al, 2000;SCOTT et al, 2001SCOTT et al, , 2010SCOTT et al, , 2012JONGEJAN et al, 2004;MORSHED et al, 2005;DUBSKA et al, 2009;ELFVING et al, 2010;HILDEBRANDT et al, 2010;KJELLAND et al, 2010;HASLE et al, 2011;HASLE, 2013;MOVILA et al, 2011;GELLER et al, 2013;CAPLIGINA et al, 2014), even introducing them to different continents (OLSEN et al, 1995b;MUKHERJEE et al, 2014;. Although the role of birds as hosts and disseminators of ticks has received much attention over the past several years, there is a lack of studies in South America, including Brazil.…”
Section: Outside Of Brazil Mainly In Europe and Northmentioning
confidence: 99%
“…(Alekseev et al, 2001; Bjöersdorff et al, 2001; Daniels et al, 2002; Ogden et al, 2008; Franke et al, 2012), Babesia spp. (Hasle et al, 2011), Rickettsia / Coxiella (Elfving et al, 2010; Socolovschi et al, 2012) and Tick-borne encephalitis virus (TBEV) (Waldenström et al, 2007; Geller et al, 2013). The prevalence of ticks on birds varies between years, season, locality and different bird species.…”
Section: Introductionmentioning
confidence: 99%
“…The first study to investigate TBEV RNA in ticks from migrating birds was done on 13,260 migrating birds on the southeast coast of Sweden in 2001, showing that 3.6% of the birds were tick-infested and TBEV RNA was detected in 4 of 1,155 investigated ticks (0.3%) [81]. A study on migrating birds in Western Estonia found that 1 of 249 investigated ticks (0.4%) were infected with TBEV [82]. Despite this low TBEV prevalence, migrating birds may be very important for spreading of TBEV over larger distances, considering that several hundred million birds migrate through Scandinavia every spring and fall [81].…”
Section: Vector-host Transmissionmentioning
confidence: 99%